Human β-Defensin 2 as a Link between EBV Infection and Multiple Sclerosis - Refaat, Aya; Younis, Hala (Iraqi Journal of Science, 2024)
Multiple sclerosis (MS) is the result of a complex interaction between environmental factors and genetic predisposition. Epstein-Barr virus (EBV) is a significant environmental risk factor associated with MS. Human- beta defensin 2 (HβD-2) is a crucial innate immune response proteint that as an inflammatory marker protects humans from pathogens invading the body like viruses. Therefore, a case-control study was conducted on 90 subjected (48 patients with MS and 42 healthy controls) to examine the role of HβD-2 in EBV viral load infection and MS patients. An enzyme-linked immunosorbentassay kit was used to measure HβD-2 levels in serum. The viral load of EBV was determined using a real-time PCR. The findings revealed that median HβD-2 levels in patients were significantly lower than in controls. (96.62 vs.124.8 ng/mL; p < 0.01). According to the receiver operating characteristic curve analysis, HβD-2 is good predictor for MS disease (area under the curve=0.739; p < 0.001). EBV frequency was lower in MS patients compared to the controls, although difference was not statistically significant (25 vs. 38.1%; p = 0.181).On other hand, the median (EBV) load was substantially greater in patients than in healthy controls ( 8.55 vs. 1.4 DNA copy/100 cells). This study concluded that HβD-2 levels showed no significant differences in each age group, sex, Expanded Disability Status Scale (EDSS) of multiple sclerosis patients, rather showed an inverse significant correlation (correlation coefficient = - 0.432) with EBV load, which protect against human viral infections.